Disguised Emotion in Alexithymia: Subjective Difficulties in Emotion Processing and Increased Empathic Distress - Nam, Gieun; Lee, Hyerin; Lee, Jang-Han; Hur, Ji-Won (Frontiers in Psychiatry, 2020)
Despite decades of speculation, many causal aspects that contribute to the heterogeneity of alexithymia still must be clarified. This study examined the extent of the alexithymia phenotype and its contribution to social function in the general population. In total, 200 participants (females = 111) completed the Toronto Alexithymia Scale-20 (TAS-20), multiple self-reporting questionnaires measuring emotion intelligence, empathy, hostility and impulsivity, and the Reading the Mind in the Eyes Test (RMET). In the multivariate analysis, highly alexithymic individuals appeared to report subjective deficits in emotion recognition and regulation as well as increased impulsivity; however, their empathy skills were intact, and even the proneness to experiencing empathic distress with others' suffering was increased among alexithymic individuals. We also compared the clinical and behavioural manifestations of highly alexithymic male and female subjects to those of each gender control group. As a result, in contrast to their subjective self-reports of emotion processing impairment, the RMET performance appeared to be preserved in alexithymic females; however, highly alexithymic males showed actual deficits in the emotion recognition task. Future research needs to further refine the constructs of alexithymia to incorporate the phenotypic changes in affected individuals in relation to measuring instruments, the extent of empathic distress, and gender.